An electrochemical sensor for 1-naphthylamine based on a novel composite of cyclodextrin-graphene and molecularly imprinted poly(vinylferrocene). Issue 7 (3rd February 2016) - Tang, Huan; Chen, Jianrong; Zeng, Yanbo; Li, Zhouyang; Huang, Hong; Li, Lei
Abstract : The preparation of GN/CD-MIPVF using vinylferrocene as a novel functional monomer for the construction of an electrochemical sensor for 1-naphthylamine determination. Abstract : A novel composite of a cyclodextrin-functionalized graphene nanosheet and molecularly imprinted poly(vinylferrocene) (GN/CD-MIPVF) was prepared. GN/CD-MIPVF employed vinylferrocene as a novel functional monomer, and it was applied to construct an electrochemical sensor for 1-naphthylamine (1-NA). Vinylferrocene as an electron mediator was covalently introduced into the surface imprinted composite to enhance the sensitivity of the GN/CD-MIPVF sensor. The GN/CD-MIPVF composite was characterized using Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, Raman spectroscopy, thermal gravimetric analysis, and scanning electron microscopy. The properties of the GN/CD-MIPVF sensor including its electrochemical behaviour, adsorption dynamics, and selectivity were evaluated by differential pulse voltammetry. The GN/CD-MIPVF composite containing ferrocene groups improved the electrocatalytic activity of its sensor and led to a higher peak current response compared to that produced by a traditional functional monomer like methacrylic acid. Under optimal conditions, the GN/CD-MIPVF sensor had a wide linear range over 1-NA concentrations from 0.3 to 100.0 μM with a detection limit of 0.1 μM (S/N = 3). The GN/CD-MIPVF sensor was satisfactorily used for the determination of 1-NA in environmental water samples.